Learners’ Needs Analysis for the Development of Reaction Rate Experimental Videos - Arinda Marganingtyas; Yuli Hartati; Farah Erika; Pintaka Kusumaningtyas; Agung Rahmadani (SEJ (Science Education Journal), 2025)
Understanding chemical reaction rates requires practical experiences that allow students to observe factors influencing reaction speed. However, limited laboratory equipment and materials in many schools hinder the implementation of meaningful experiments. This study aims to determine the learning media needs of Class XI students for the development of reaction rate experimental videos at SMA Negeri 7 Malinau. A total of 17 students (n = 17) and one science teacher participated in the study. Data were collected using questionnaires and interviews, then analyzed through descriptive, qualitative, and quantitative approaches. The results show that 88.24% of students experience difficulties in learning reaction rate concepts, 76.47% perceive that videos help their understanding, and 100% agree that experimental videos are needed as learning resources. These findings highlight the urgent need for offline, visually engaging, and easy-to-understand experimental videos to support students’ conceptual understanding in contexts with limited laboratory facilities. The results of this needs analysis will directly inform the content design, structure, and visual features of the reaction rate experimental videos to be developed.